Tinau River Conservation and Integrated Water Resource Management - Poudel, Som Nath (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
This paper explores the lives of Tinau River and its inter-dependence with the basin communities and ecosystems in a holistic perspective. It seeks to share the influences of changing natural and anthropogenic processes on the river-catchment and how the resultant changes in river-basin influence the livelihoods and ecosystems. Taking an integrated approach of river-basin management, it aims to enhance basin-literacy by linking the ongoing processes in river-catchment, land use pattern and human activities. Without environmentally-sound and sustainable integrated river basin management, it will not be possible to achieve self-sufficiency in food and energy. Tinau River management and conservation must aim to have a healthy river. Each type of water/resource use in the basin is managed in a fragmented manner by a separate department or agency. For healthy watershed development water resources of the river should be managed in a comprehensive manner. Policies, framework, methodology, legislation and institutions are to be developed and established for Integrated Water Resource Management (IWRM) of the river. DOI: http://dx.doi.org/10.3126/hn.v10i0.7099 Hydro Nepal Vol.10 January 2012 24-31